Application Of Online Learning Based On Realistic Mathematic Education (RME) Assisted Animation Media In Improving Learning Outcome Of Students in Class IV Elementary School - Amir, Titin Handayani; Syamsuddin, Agustan; Sulfansyah, Sulfansyah (Jurnal Ilmiah Sekolah Dasar, 2021)
This study aimed to determine the influence of the Realistic Mathematical Education (RME) approach assisted by animation media on mathematics learning outcomes of fourth grade elementary school students, Manggala District, Makassar in academic year of 2020/2021. This study was a quantitative research by using a quasi-experimental research design with a non-equivalent control group design. There were 30 students involved as the research sample with a simple random sampling technique (Simple Random Sampling). The data were collected using observation and written tests by giving five essay questions with different points for each question. This research was conducted by giving a pretest as a result of initial learning before being given treatment and by giving a post-test as a result of the given treatment at the end of the meeting. Furthermore, the data obtained were analyzed using the SPSS v.22 application by looking for the results of the normality test, homogeneity test, N-Gain test and finally the paired sample t-test (Paired Sample Test) to test the hypothesis.The students’ average score before applying Realistic Mathematics Education (RME) approach assisted by animation media it was 69.67 included in the less category. After applying Realistic Mathematical Education (RME) assisted by animation media, the results showed that there was a difference in the students' average scores. By applying the Realistic Mathematical Education (RME) approach assisted by animation media, the students’ average score, the students obtained an average score of 74.60 included in the medium category. This can be proven in the t-test output and it was known that the tcount = 7,170 with Sig(2-tailed) = 0.000 and the ttable = 2.05 then tcount = 7,170 > ttable = 2.05 while the significance value was 0.000 <0.05, meaning H1 was accepted and H0 rejected.